2020
DOI: 10.1523/eneuro.0076-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

diceCT: A Valuable Technique to Study the Nervous System of Fish

Abstract: Contrast-enhanced X-ray imaging provides a non-destructive and flexible approach to optimizing contrast in soft tissues, especially when incorporated with Lugol’s solution (aqueous I 2 KI), a technique currently referred to as diffusible iodine-based contrast-enhanced computed tomography (diceCT). This stain exhibits high rates of penetration and results in excellent contrast between and within soft tissues, including the central nervous system. Here, we present a staining method for opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 59 publications
0
8
0
1
Order By: Relevance
“…We measured internal metrics of the olfactory system, including the volume of the excurrent channel (Figures 9 and 11; Table 3). A recent study using diceCT to examine an elasmobranch nervous system reported a shrinkage of 14% for brain tissue in their specimens ( Chiloscyllium punctatum ; Camilieri‐Asch, Shaw, et al, 2020). While the diceCT protocol differed from this study, such as choice of fixative and percentage of Lugol's iodine used, their results suggest that the excurrent channel measured could be partially affected by tissue shrinkage during preservation.…”
Section: Discussionmentioning
confidence: 99%
“…We measured internal metrics of the olfactory system, including the volume of the excurrent channel (Figures 9 and 11; Table 3). A recent study using diceCT to examine an elasmobranch nervous system reported a shrinkage of 14% for brain tissue in their specimens ( Chiloscyllium punctatum ; Camilieri‐Asch, Shaw, et al, 2020). While the diceCT protocol differed from this study, such as choice of fixative and percentage of Lugol's iodine used, their results suggest that the excurrent channel measured could be partially affected by tissue shrinkage during preservation.…”
Section: Discussionmentioning
confidence: 99%
“…We used a diffusible iodine-based technique to enhance contrast of soft tissues for diffusible iodine-based contrast-enhanced computed tomography (diceCT). Increased time penetration of Lugol's iodine (aqueous I2KI, 1% I 2 , 2% KI) offers possibilities to visualize between and within soft tissue structures (Camilieri-Asch et al, 2020 ). The temporal bone was fixed in a modified Karnovsky's fixative solution of 2.5% glutaraldehyde, 1% paraformaldehyde, 4% sucrose, and 1% dimethyl sulfoxide in 0.13 M of Sorensen's phosphate buffer.…”
Section: Methodsmentioning
confidence: 99%
“…We used a diffusible iodine-based technique to enhance contrast of soft tissues for diffusible iodine-based contrast-enhanced computed tomography (diceCT). Increased time penetration of Lugol's iodine (aqueous I2KI, 1% I 2 , 2% KI) provided possibilities to visualize between and within soft tissue structures ( 24 ). The temporal bone was fixed in a modified Karnovsky's fixative solution of 2.5% glutaraldehyde, 1% paraformaldehyde, 4% sucrose, and 1% dimethyl sulfoxide in 0.13 M of Sorensen's phosphate buffer.…”
Section: Methodsmentioning
confidence: 99%